MORPHOLOGICAL ASSESSMENT OF APOPTOSIS AND NECROSIS SIGNS IN THE GASTRIC MUCOSA IN A MODEL OF HEPATORENAL SYNDROME (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Background: Hepatorenal syndrome (HRS) is a severe complication of advanced liver disease characterized by functional renal failure and profound systemic hemodynamic disturbances. These alterations may significantly affect gastrointestinal organs, particularly the gastric mucosa. However, the mechanisms of epithelial injury and the balance between apoptosis and necrosis in the gastric mucosa during HRS remain insufficiently studied. Objective: The aim of this study was to evaluate morphological manifestations of apoptosis and necrosis in the gastric mucosa in an experimental model of hepatorenal syndrome. Materials and Methods: Sixty male Wistar rats were divided into three groups: sham-operated control (n=20), cirrhosis group induced by common bile duct ligation (n=20), and hepatorenal syndrome group (n=20), where acute-on-chronic liver failure and renal dysfunction were induced using carbon tetrachloride following bile duct ligation. Gastric tissues were collected on day 28. Histological examination was performed using hematoxylin–eosin staining to detect necrotic changes. Apoptosis was evaluated using the TUNEL assay. Immunohistochemical analysis assessed the expression of apoptosis-related proteins including Bax, Bcl-2, and cleaved caspase-3. Results: The HRS group demonstrated the most severe gastric mucosal damage. The apoptotic index increased significantly from 4.2±1.1 in controls to 18.5±3.4 in the cirrhosis group and 34.7±5.2 in the HRS group (p